Context and culture via cohesive devices in higher education students’ and professional writers’ opinion articles - Abu-Ayyash, Emad A. S. (Penerbit Universiti Kebangsaan Malaysia, 2020)
The literature on cohesive devices is marked with evident dearth in studies that consider the context-text ties. The current paper attempts to fill this gap, and, therefore, combat an idealised ‘villain’ in research, which is confining textual analysis to in-text relations. The study propounds the idea of expanding the analysis to include ties between the written text and the surrounding context and culture. The specific purpose is to explore the use and function of the cohesive devices which link the text to the context (exophora) and the ones that relate the text to the culture (homophora). The methodology involved explaining the cohesive devices to a postgraduate TESOL class of eight students (non-native speakers of English) in one of the universities in the UAE. After that, the students were asked to work in pairs and produce four opinion articles about a recent newspaper topic of their choice. They selected the United Kingdom Independent Party (UKIP) leader’s call to ban the burqa in the UK. In addition, two articles from the Independent and the Guardian on the same topic were also discussed. Comparative analysis was conducted on the six articles vis-à-vis the use and functions of cohesive devices. The analysis involved four categories: person deixis, spatial deixis, temporal deixis, and the definite article. The findings showed that exophoric and homopohric cohesive devices were employed abundantly, with exophora occurring in more instances. The study also revealed the relevant functions that have evident implications about assumptive and supportive roles of cohesive devices.